In situ atomic force microscopy study of polypyrrole synthesis and the volume changes induced by oxidation and reduction of the polymer - Suarez, M; Compton, R (1999)
The morphology changes of polypyrrole (PPy) films on polycrystalline platinum, glassy carbon and gold electrodes during synthesis and oxidation-reduction processes have been investigated using in-situ electrochemical AFM. It is found that the morphology of the film at the first stages of synthesis depends on the nature of the electrode and it is different from that of the thick film morphology. Remarkable changes in the morphology of PPy films were observed following synthesis suggesting that PPy films have an extraordinary capacity to alter their morphology over time. Upon reduction (undoping) in aqueous solution of NaClO4, a perchlorate-doped PPy undergoes initially rapid swelling and subsequent continuous slow shrinking during the first reduction potential step from 0.2 to -0.8 V, but during subsequent redox potential steps no remarkable changes of volume are observed. In contrast, in an aqueous solution of sodium p-toluenesulfonate, the polymer swells on reduction and shrinks on oxidation during continuous redox potential steps between 0.2 and -0.8 V. © 1999 Elsevier Science S.A.